The Cellular Localization of GnRH and LHR in Aged Female Mice - Young-Jong Kim; Byung-Joon Park; Won-Jae Lee; Seung-Joon Kim (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Gonadotropin releasing hormone (GnRH) centrally plays a role in control of the hypothalamicpituitary-gonadal axis-related hormone secretions in the reproductive neuroendocrine system. In addition, hormone receptors like luteinizing hormone receptor (LHR) are important element for hormones to take effect in target organ. However, ageing-dependent changes in terms of the distribution of GnRH neurons in the brain and LHR expression in the acyclic ovary have not been fully understood yet. Therefore, we comparatively investigated those ageing-dependent changes using young (1-5 months), middle (11-14 months) and old (21-27 months) aged female mice. Whereas a number of GnRH positive fibers and neurons with monopolar or bipolar morphology were abundantly observed in the brain of the young and middle aged mice, a few GnRH positive neurons with multiple dendrites were observed in the old aged mice. In addition, acyclic ovary without repeated development and degeneration of the follicles was shown in the old aged mice than others. LHR expression was localized in theca cells, granulosa cell, corpora lutea and atretic follicle in the ovaries from young and middle aged mice, in contrast, old aged mice had few positive LHR expression on the follicles due to acyclic ovary. However, the whole protein level of LHR was higher in the ovary of old aged mice than others. These results are expected to be used as an important basis on the relationship between GnRH and LHR in old aged animals as well as in further research for reproduction failure.